AI-POWERED TASK AUTOMATION AND ASSISTANCE ON LINUX - Rawat, Ankita; Chaprana, Kirti; Kumari, Kshama; Aggarwal, Ruchika (International Journal of Research -GRANTHAALAYAH, 2024)
This research presents the design and development of Jarvis, an intelligent personal assistant tailored for Linux-based systems. Inspired by virtual assistants like Cortana and Siri, Jarvis offers a user-friendly interface for executing a wide range of daily tasks via voice or text input. The system integrates modules for speech recognition, text-to-speech synthesis, web automation, and machine learning-based command interpretation. Jarvis facilitates activities such as general conversation, online searches, weather updates, health inquiries, and event reminders. By combining Python libraries like speech_recognition, pyttsx3, pywhatkit, and wikipedia, the assistant ensures seamless interaction and efficient task execution. The layered architecture—from user input to system-level operations—enables robust, real-time responses, making Jarvis a practical and scalable solution for enhancing Linux user productivity.